Study effect of welding current on mechanical properties of galvanized steel sheets in resistance spotwelding - Muhammad Rifki Ismail
This final year project is about the effect of welding current and the cycles on the quality of weld joint on galvanized steel sheets using resistance spot welding. Examinations involve tensile shear and tensile peel strength (T-peel test) of the galvanized steel sheet that have about 3.0mm in thickness. The goal of this research is to examine the behavior of the spot welding on the galvanized steel sheet to avoid the corrosion problem in automobile industries.